AN ANALYSIS OF THE EFFECT OF AN AUDITORâS PERSONALITY TYPE TO AUDIT QUALITY AND PROFESSIONAL SKEPTICISM AS THE MEDIATING VARIABLE - Firza, Edy (Universitas Jambi, 2014)
The issue of audit quality is still arguable because of different views on audit quality. Different views lead to different definitions as well as different measurements. One of the factors affecting it is the auditor.Â Audit quality is influenced by professional skepticism, while that professional skepticism is affected by auditorâs personality type. Theoretically, personality type has indirect effect on audit quality through professional skepticism. The respondents of this study were fifty three auditors from audit firm in Yogyakarta and Surakarta.Â Data were collected and analyzed with regression analysis to investigate the relationship, the Sobelâs test to find out the significance of mediation effect, and Bartolâs approach to know the significance of partial mediation.Â The study found out that (1) intuition, thinking and judging personality types affect professional skepticism, (2) this skepticism positively related to audit quality, and (3) partial mediation has its effects on thinking and judging personality types.